2022
DOI: 10.1038/s41467-022-31501-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor paralogs orchestrate alternative gene regulatory networks by context-dependent cooperation with multiple cofactors

Abstract: In eukaryotes, members of transcription factor families often exhibit similar DNA binding properties in vitro, yet orchestrate paralog-specific gene regulatory networks in vivo. The serially homologous first (T1) and third (T3) thoracic legs of Drosophila, which are specified by the Hox proteins Scr and Ubx, respectively, offer a unique opportunity to address this paradox in vivo. Genome-wide analyses using epitope-tagged alleles of both Hox loci in the T1 and T3 leg imaginal discs, the precursors to the adult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…Our study of the Dfd-regulated AP-2 enhancer challenges the current view that Hox specificity is achieved with low-affinity binding sites. This is consistent with a very recent study showing that the anterior Hox protein Sex combs reduced (Scr) in combination with its cofactor Exd recognize Scr–Exd high-affinity sites to specifically control target genes in the leg primordium of thoracic segment 1 35 . Thus, it seems that Hox TFs employ a wider range of mechanisms to ensure the specific activation of their targets.…”
Section: Discussionsupporting
confidence: 92%
“…Our study of the Dfd-regulated AP-2 enhancer challenges the current view that Hox specificity is achieved with low-affinity binding sites. This is consistent with a very recent study showing that the anterior Hox protein Sex combs reduced (Scr) in combination with its cofactor Exd recognize Scr–Exd high-affinity sites to specifically control target genes in the leg primordium of thoracic segment 1 35 . Thus, it seems that Hox TFs employ a wider range of mechanisms to ensure the specific activation of their targets.…”
Section: Discussionsupporting
confidence: 92%
“…7). Given the presence of putative Exd-Ubx dimer binding sites in the VT42733 sequence, this may involve Ubx autoregulation of this enhancer in proximal dorsal anterior cells as shown for Exd-Ubx and Exd-Scr binding in other appendages [20,73,74]. However, Exd-Ubx binding to abx represses Ubx expression proximally in halteres [20] whereas our results indicate that Exd positively regulates Ubx in T2 and T3 femurs.…”
Section: Discussionmentioning
confidence: 48%
“…It has recently been reported that Dll can act as co-factor for Scr to help regulate T1 morphology [73]. Dll and Scr bind to two monomer sites separated by a short space in enhancers of Scr target genes in T1 cells [72].…”
Section: Candidate Tfs For Ubx Regulation During Pupal Leg Developmentmentioning
confidence: 99%
“…This suggests that Hth is required for Ubx mediated repression of trichomes and bristles in the proximal posterior and proximal dorsal-anterior but Exd is only required in the latter cells ( Figure 7 ). Given the presence of putative Exd-Ubx dimer binding sites in the VT42733 sequence, this may involve Ubx autoregulation of this enhancer in proximal dorsal-anterior cells as shown for Exd-Ubx and Exd-Scr binding in other appendages ( Mann, 1995 ; Delker et al, 2019 ; Feng et al, 2022 ). However, Exd-Ubx binding to abx represses Ubx expression proximally in halteres ( Delker et al, 2019 ) whereas our results indicate that Exd positively regulates Ubx in T2 and T3 femurs.…”
Section: Discussionmentioning
confidence: 90%